Pengaruh Kompetensi Pelatihan dan Supervisi Terhadap Kinerja Karyawan Pada Industri Perhotelan Di Kota Palopo - Muh Arif Andi Manrang; Saharuddin Saharuddin; Rahmad Solling Hamid (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This study aims to determine the effect of competence, training and supervision on employee performance. The object of research is all hospitality agencies in the city of Palopo. The population is 17 hotels. Determination of the sample purposive sampling technique is the technique of determining the sample with certain considerations. Collecting data using a questionnaire with data analysis using multiple linear regression. using the help of SPSS version 20. The results show that: First, competence has a significant influence on employee performance. Second, training has a significant effect on employee performance. Third, supervision has a significant effect on employee performance.